The history of science from the philosophical point of view - Stanislav Z. Pakulyak; Vitaly G. Gorokhov (Высшее образование в России)
The authors substantiate the importance of the postgraduate course “The history andphilosophy of science” for future scientists irrespective of their specialty. This course forms the general notion of science, its history and developmental trends, trains a postgraduate student to self-reflection, develops intellectual and cultural outlook of a future researcher.